2004
DOI: 10.3748/wjg.v10.i1.136
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative cimetidine administration promotes peripheral blood lymphocytes and tumor infiltrating lymphocytes in patients with gastrointestinal cancer: Results of a randomized controlled clinical trial

Abstract: AIM:To study the effects of perioperative administration of cimetidine (CIM) on peripheral blood lymphocytes, natural killer (NK) cells and tumor infiltrating lymphocytes (TIL) in patients with gastrointestinal (GI) cancer. METHODS:Forty-nine GI cancer patients were randomized into treatment group, who took CIM in perioperative period, and control group, who did not take the drug. The treatment was initiated 7 days before operation and continued for 10 days after surgery. At baseline examination before operati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 54 publications
1
35
0
2
Order By: Relevance
“…Cimetidine has demonstrated immunomodulatory effects in a number of studies (32)(33)(34)(35)(36), while histamine has been shown to have immunosuppressive effects (37,38). These results suggest that the effect of cimetidine on immunity is mediated by blocking the immunosuppressive effect of histamine via the H 2 receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Cimetidine has demonstrated immunomodulatory effects in a number of studies (32)(33)(34)(35)(36), while histamine has been shown to have immunosuppressive effects (37,38). These results suggest that the effect of cimetidine on immunity is mediated by blocking the immunosuppressive effect of histamine via the H 2 receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the exaggerated post-operative immune suppression experienced in patients with CRC is in part mediated by histamine release (9). The use of H2RAs has been shown to abrogate tumour-associated systemic immune suppression [ Table 3], with restoration of circulating levels and activity of T-lymphocyte and NK cell subsets (116), potentially via augmentation of IL-2 and interferon activity.…”
Section: Systemic Inflammationmentioning
confidence: 99%
“…Impaired cell-mediated immunity is common in cancer patients (8). Particularly in patients undergoing surgical resection of CRC, that is recognised to attenuate post-operative cell-mediated immunity (9), this may be an important mechanism by which disseminated or shed tumour cells evade effective immunosurveillance and establish de novo metastases (10)(11)(12). Furthermore, the presence of a systemic inflammatory response has been associated with a poorer response to chemotherapeutic agents and an increased risk of toxicity (13).…”
Section: Introductionmentioning
confidence: 99%
“…Gastric cancer patients also have higher levels of suppressor lymphocyte activity when compared to normal controls, and these levels are restored to normal with CIM treatment (42). In a controlled randomized clinical trial, Lin et al (43) recently showed that pre-operative CIM administration at the dose of 400 mg/day promoted peripheral blood lymphocytes and tumor infiltrating lymphocytes in patients with gastrointestinal cancer.…”
Section: Mechanisms Of Action Of Cimetidine In Oncologymentioning
confidence: 99%